Differences in Physicochemical and Nutritional Properties of Breast and Thigh Meat from Crossbred Chickens, Commercial Broilers, and Spent Hens - Chen, Yulian (Asian-Australas J Anim Sci, 2016)
The objective of this study was to compare the physicochemical and nutritional properties of breast and thigh meat from commercial Chinese crossbred chickens (817 Crossbred chicken, 817C), imported commercial broilers (Arbor Acres broiler, AAB), and commercial spent hens (Hyline Brown, HLB). The crossbred chickens, commercial broilers and spent hens were slaughtered at their typical market ages of 45 d, 40 d, and 560 d, respectively. The results revealed that several different characteristic features for the three breeds. The meat of the 817C was darker than that of the other two genotypes. The 817C were also characterized by higher protein, lower intramuscular fat, and better texture attributes (cooking loss, pressing loss and Warner-Bratzler shear force [WBSF]) compared with AAB and HLB. The meat of the spent hens (i.e. HLB) was higher in WBSF and total collagen content than meat of the crossbred chickens and imported broilers. Furthermore, correlation analysis and principal component analysis revealed that there was a clear relationship among physicochemical properties of chicken meats. With regard to nutritional properties, it was found that 817C and HLB exhibited higher contents of essential amino acids and essential/non-essential amino acid ratios. In addition, 817C were noted to have highest content of microelements whereas AAB have highest content of potassium. Besides, 817C birds had particularly higher proportions of desirable fatty acids, essential fatty acids, polyunsaturated/saturated and (18:0+18:1)/16:0 ratios. The present study also revealed that there were significant differences on breast meat and thigh meat for the physicochemical and nutritional properties, regardless of chicken breeds. In conclusion, meat of crossbred chickens has some unique features and exhibited more advantages over commercial broilers and spent hens. Therefore, the current investigation would provide valuable information for the chicken meat product processing, and influence the consumption of different chicken meat.